Advanced Life Support Video Training Modalities: A Literature Review - Adnyani, Putu Desi; Agustini, Ni Luh Putu Inca Buntari; Wahyunadi, Ni Made Dewi; Sanjana, I Wayan Edi; Artawan, I Kadek (Babali Publisher, 2023)
Introduction: Knowledge and skills of health workers regarding Advanced Life Support (ALS) are an important part that needs to be trained and improved with appropriate training modalities in handling cardiac arrest patients. This literature review aims to find out which modalities are the most effectively applied to ALS training which can increase the knowledge and skills of health workers in conducting ALS. Methods: Literature study using 11 articles that have been published and peer-reviewed from data-based PubMed, CINAHL, and ScienceDirect using the keywords effectiveness, advanced life support, modalities, nurses, knowledge, and skills. Searches were limited to full text articles, experimental designs, publications from 2017 to 2022. Selection of articles in research using flowchart Prisma.Results: Analysis of eleven articles or journals related to the research objectives found that the video training was the most effective methods in increasing the knowledge and skills of respondents in ALS training. The implementation of ALS training in a hybrid manner, namely the use of non-face-to-face learning methods using video with face-to-face training led by an instructor, showed no significant difference, but video training was preferred because it provides convenience regarding time, place of implementation, and more training participants. Conclusion: ALS training must be given to nurses at least once a year, so it can be suggested to institutions to use the learning video method as a method of providing training.